1994
DOI: 10.1007/bf00044687
|View full text |Cite
|
Sign up to set email alerts
|

Vertical structure of seed banks and the impact of depth of burial on recruitment in two temporary marshes

Abstract: The structure of the seed bank (including Chara oospores), in relation to depth within the sediment and disturbance, was studied in two Rh6ne delta temporary marshes for two years. The seeds of all species were concentrated in the top 2 cm of sediment with very low numbers beeing found below 4 cm. When an exclosure eliminated disturbances of the sediment by animals, the vertical repartition of seeds at site 2 was more pronounced than outside the exclosure.In experiment 1, the emergence capacity of seeds from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 35 publications
9
39
1
Order By: Relevance
“…Surprisingly, the emergence of P. ochreatus seed was limited to depths less than half that of C. globularis oospores which were l/30th the mass. However, this result is in keeping with Bonis & Lepart's (1994) findings that charophyte oospores emerged from depths (40 mm) in excess of the larger propagules of vascular species tested. They suggested that elongation by the single-celled protonema following oospore germination was a more energy efficient method of emergence than multicellular growth exhibited by angiosperm seedlings.…”
Section: Specific Burial Limits To Emergencesupporting
confidence: 89%
See 2 more Smart Citations
“…Surprisingly, the emergence of P. ochreatus seed was limited to depths less than half that of C. globularis oospores which were l/30th the mass. However, this result is in keeping with Bonis & Lepart's (1994) findings that charophyte oospores emerged from depths (40 mm) in excess of the larger propagules of vascular species tested. They suggested that elongation by the single-celled protonema following oospore germination was a more energy efficient method of emergence than multicellular growth exhibited by angiosperm seedlings.…”
Section: Specific Burial Limits To Emergencesupporting
confidence: 89%
“…Comparable investigations of burial limits for emergence of submerged seedlings are few, however Bonis & Lepart (1994) also describe a declining seedling response with burial depth ranging from 0 to 40 mm for propagules of four taxa that included one charophyte. In contrast, van den Berg et al (1999) found that germling response increased with burial depth over 0-5 mm for oospores of a Chara species, collected from Lake Veluwemeer, the Netherlands.…”
Section: Emergence Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruppia maritima has a broad distribution (the Mediterranean: e.g., Bonis and Lepart, 1994; both sides of the Atlantic: e.g., Orth and Moore, 1988;Figuerola et al, 2002; the Pacific: e.g., Bigley and Harrison, 1986) and is common in the northern Gulf of Mexico (Eleuterius, 1987;Cho and Poirrier, 2005). Other species of SAV are also present in the northern Gulf of Mexico (e.g., Thalassia testudinum and Halodule wrightii; Eleuterius, 1987), but R. maritima's broad salinity tolerance allows it to inhabit areas with heavy freshwater input such as Lake Pontchartrain (Cho and Poirrier, 2005) and the nearshore habitats around Mobile Bay (Johnson et al, 2006), making it a dominant species in many of these areas.…”
Section: S Ubmerged Aquatic Vegetation (Sav)mentioning
confidence: 99%
“…Seeds germinate from the winter through early spring and recruitment is frequently from seeds (Cho and Poirrier, 2005). Seeds can apparently remain dormant and viable in the sediments for several years and germinate when conditions are appropriate, though more deeply buried seeds (reviewed in Kantrud, 1991;Bonis and Lepart, 1994) and older seeds (Bonis and Lepart, 1994) are less likely to germinate. The species acts much like an annual plant in many years, although it can also regenerate in the spring from overwintering rhizomes (Dunton, 1990;Cho and Poirrier, 2005).…”
Section: S Ubmerged Aquatic Vegetation (Sav)mentioning
confidence: 99%